AI-Generated Child Pornography: Legal Challenges in Digital Age - Sergey S. Zhevlakovich; Ivan S. Lukinsky; Alina V. Sumina (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
As digital technologies penetrate all spheres of human life, scientific and technological progress becomes a global development factor. Artificial intelligence (AI) is an advanced and rapidly developing area that has already proved its efficiency in healthcare, finance, and transport. However, AI also poses significant ethical and legal challenges because it can be used to generate and distribute virtual child pornography. The article features methods of generating virtual child pornography through various AI tools, their ethical implications, and the existing legal frameworks that cover these issues. In fact, the existing international and national laws on child abuse fail to take into account AI-generated images. The authors studied cases and legal precedents to highlight the urgent need for robust regulatory legal measures to prevent the misuse of AI technologies, the potential of which should be realized for the benefit of society.